Highly Efficient Etherification of Silanes by Using a Gold Nanoparticle Catalyst: Remarkable Effect of O2. Issue 43 (24th September 2013) - Mitsudome, Takato; Yamamoto, Yuya; Noujima, Akifumi; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
<x xml:space="preserve">Abstract</x> O2 is acting! A nanosized hydroxylapatite‐supported Au nanoparticle (NP) catalyst exhibited high activity under aerobic conditions, and various silyl ethers could be obtained from diverse combinations of silanes with alcohols. Moreover, O2 was found to act not as a stoichiometric oxidizing reagent, but as a non‐consumed promoter, significantly boosting the catalytic activity of AuNPs (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>